Effects of low-dose combined olanzapine and sertraline on negative and depressive symptoms in treatment-resistant outpatients with acute exacerbated schizophrenia - Lang, Xiaoe; Zang, Xiaocui; Yu, Feng; Xiu, Meihong (Frontiers in Pharmacology, 2023)
Background: Treatment-resistant schizophrenia (TRS) is a major clinical challenge. Current antipsychotics inadequately affect negative and depressive symptoms in patients with TRS. Thus, novel treatments are needed. This study examined the efficacy of low-dose combined olanzapine (OLA) and sertraline on depressive and negative symptoms in patients with TRS. Methods: Thirty-four TRS outpatients with acute exacerbation schizophrenia were randomly assigned to OLA monotherapy (12.5–20 mg/day) (control group) or low-dose combined OLA (7.5–10 mg/day) and sertraline (50–100 mg/day) (OS group). Clinical symptoms were assessed by the Positive and Negative Syndrome Scale (PANSS) at baseline and the end of treatment weeks 4, 8, 12, and 24. Depressive symptoms and social functioning were also assessed. Results: Compared with the control group, the OS group showed significant improvements in depressive and negative symptoms over time. Additionally, low-dose combined OLA and sertraline significantly increased social functioning compared with OLA monotherapy. There were no significant between-group differences in improved psychotic symptoms. However, the reduced total Hamilton Depression Rating Scale score and PANSS negative subscore were unassociated with social functioning improvements, suggesting that these effects of combination treatment are independent. Conclusions: Low-dose combined OLA and sertraline may be effective for treating negative and depressive symptoms compared with standard OLA monotherapy in patients with TRS who are experiencing acute exacerbation schizophrenia.